(untitled) (应用人工智能研究, 2025)
Along with the rapid development of information technology, there are unprecedented opportunities and challenges in the area of chronic diseases. Chronic diseases’ long-term nature, complexity and impact on patients’ quality of life make it clear that traditional prevention model can not meet patients’ diverse needs and increase their trust. It aims at providing personalized and accurate prevention and treatment plans based on AI, Big Data, Internet of Things, and other advanced technologies in order to improve doctor-patient trust. In this paper, we deeply discuss the system’s overall structure, design, main functions, and its application effect on patients’ trust dilemma.